Practitioner research for educators : a guide to improving classrooms and schools - Robinson, V. M. 4 0 (Viviane M.)16; Lai, Mei Kuin; 5 (Thousand Oaks, California : Corwin Press, 2006)
An introduction to the technique of practitioner inquiry, discussing why it is important for educators to conduct their own research, presenting the problem-based methodology as a framework teachers can use to investigate and improve their own practices, and including detailed information on how to do a research project.
Includes bibliographical references and index.
Professional.
Keywords: 2 -- 0; 6; Research;Research -- Education;Teaching;School improvement programs;School improvement programs. -- United States.;United States.;United States; 20; 2